Environmental Legal Politics in Determining State Policies on Environmental Protection Instruments - Asriani Asriani; Salma Laitupa; Rezki Amalia; Eka Dewi Kartika (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
This study aims to analyze the influence of legal politics on the effectiveness of environmental protection instruments in Indonesia. The research focuses on how the orientation of legal politics determines the formulation, implementation, and enforcement of environmental regulations, particularly in the context of environmental licensing, supervision, and environmental economic instruments. This study employs a normative legal research method using statutory, conceptual, and policy approaches. Legal materials were obtained through library research, including legislation, scientific literature, and research findings related to environmental law and legal politics. The results of the study indicate that, normatively, Indonesia has established a relatively comprehensive regulatory framework for environmental protection. However, the effectiveness of the implementation of environmental protection instruments is still influenced by the orientation of legal politics, which tends to prioritize economic development and investment interests. This condition has led to the weakening of environmental protection instruments, which in practice are often reduced to mere administrative formalities. The novelty of this study lies in its systematic and integrative analysis of the relationship between the direction of legal politics and the effectiveness of environmental protection instruments. This study concludes that the effectiveness of environmental protection does not solely depend on the completeness of regulations but also on the consistency of legal politics in positioning sustainability principles as a priority in state policy.